Trade as an engine of creative destruction: Mexican experience with Chinese competition - Iacovone, Leonardo; Rauch, Ferdinand; Winters, L. Alan (Journal of international economics, 2013)
This paper exploits the surge in Chinese exports from 1994 to 2004 to evaluate the effects of a competition shock from a low wage competitor for producers in an important middle-income country, Mexico. We find that this shock causes selection and reallocation at both firm and product levels and that its impact is highly heterogeneous at the intensive and extensive margins. Sales of smaller plants and more marginal products are compressed and are more likely to cease, whereas those of larger plants and core products seem relatively impervious to the shock. This implies a reallocation in terms of market shares within firms and between firms. We also show that the impact of expanded access to cheaper Chinese intermediate inputs has a similar effect, with larger plants benefiting more from the availability of cheaper imported inputs.
Online veröffentlicht am 20. September 2012
Gesehen am 14.03.2023